Model Pembelajaran Digital Integratif Berbasis Literasi Kesehatan dalam Peningkatan Literasi dan Kemandirian Belajar Anak Usia Dini - Prima Trisna Aji; Elinda Rizkasari (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Abstract. This study is motivated by the low level of literacy and learning independence among early childhood learners, as well as the limited use of digital educational media integrated with health literacy. Health literacy plays an important role in shaping healthy behavior from an early age, yet it is still rarely incorporated into early childhood learning processes. This study aims to analyze the effectiveness of interactive digital learning media based on health literacy in improving literacy and learning independence among early childhood learners. This study employed a quasi-experimental design using a pretest and posttest approach with a control group. The subjects were early childhood learners divided into experimental and control groups. Data were collected through observation instruments and assessment sheets that had been tested for validity and reliability. Data analysis was conducted using parametric statistical tests to determine differences between groups. The results showed that interactive digital learning media based on health literacy significantly improved literacy and learning independence among early childhood learners. These findings indicate that integrating health literacy into digital learning media can serve as an innovative approach to support optimal child development.